Antioxidant and Lipoxygenase Inhibiting New Iridoid Glucosides from Caryopteris Odorata - Akhtar, Muhammad Nadeem; Shahzadi, Tayyab; Abbasi, Muhammad Athar; Ur-Rehman, Aziz; Riaz, Tauheed; Khan, Khalid Mohammed; Mohd Ashraf, Ahmad; Afzal, Iftikhar; Ajaib, Muhammad (Taylor & Francis, 2013)
The phytochemical investigation of the ethylacetate-soluble fraction of Caryopteris odorata (Ham. ex Roxb.) led to the isolation of four new iridoid glucosides (1–4): 8-O-trans-cinnamoyl caryoptoside (1), 8-O-trans-cinnamoyl shanzhiside methylester (2), 8-O-trans-cinnamoyl mussaenoside (3) and 8-O-cafeoyl massenoside (4). The structures of these compounds were determined by FAB-MS, IR, 1D and 2D-NMR spectroscopy and by comparing with the published data of the closely related compounds. The antioxidant potential of the isolated iridoids (1–4) was evaluated relative to conventionally used standards and these molecules exhibited good antioxidant potential. Moreover, their inhibitory potential was also screened against three enzymes, namely acetyl cholinesterase, butyrylcholinesterase and lipoxygenase. These iridoid glucosides were found to be inactive against acetyl and butyrylcholinesterases but active against lipoxygenase.